Analysis of the Effectiveness of Using Instagram as a Promotional Media for Hagu Coffee & Space - Hartoyo; Syafitri, Utami Syah; Fitrawan, Fakhry Muhammad (Ilomata International Journal of Management, 2025)
Instagram is the most widely used social media in indonesia, however, its existence is still doubted in terms of the effectiveness of a company's product marketing. The purpose of this study is to analyze the characteristics of Hagu Coffee & Space followers; analyze the level of effectiveness of using Instagram social media as a promotional media; and analyze the relationship between the characteristics of Hagu Coffee & Space followers and the level of effectiveness of using Instagram social media as a promotional media. This study uses primary data obtained through interviews and questionnaires, while secondary data is obtained from literature studies. Data analysis consists of descriptive analysis, validity test, reliability, correlation and chi square with SPSS 25 analysis tool. The promotion carried out by Hagu Coffee & Space is quite effective especially on attention and interest, but respondents do not search and immediately take action by coming directly to Hagu Coffee & Space until finally sharing information. The Bundling Ramadhan & Iftar promotion is more popular than the Fit You! promo, with visual design and promo relevance being crucial factors in attraction.